The symbolism of the visual image in the philosophical conceptions of E. Cassirer and C. Langer: the cultural context - S. P. Stoian (Ukrainian Cultural Studies, 2017)
It’s mentioned that the European atmosphere of increased interest in the problems of symbol and symbolism in the cultural space, giving rise in the second half of the XIX century to the registration of symbolism in art direction also contributes to a number of philosophical studies to the rethinking of the functioning of the cultural sphere, as well asthe whole of human existence from the standpoint of symbolism.A powerful concept that gives us an understanding of the global symbolic basis of culture is the theory of E. Cassirer, which he outlines in his work "The Philosophy of symbolic forms", expanding these issues infurther series of works collected under the title "An Essay on Man". Cassirer’s views are one of the main methodological foundations in our research, because the human culture has deeply symbolic character and consists of various symbolic forms, among which art takes a special place. Culture is not something predetermined; it is created by a person who is gradually separated from the natural world precisely because of its ability for continuous production of symbols. Along with the myth Cassirer distinguished such symbolic forms as language, art, science, through which the essential components of the symbolic reality of man are also produced. In work "Philosophy of Symbolic Forms", the art is mentioned in the context of consideration of the specificity of these symbolic realms and researcher focuses on myth, language and the problem of scientific knowledge. The philosopher indicates the communicative function of art, which becomes extremely important in the twentieth century in the context of the active involvement of the viewer in the process of co-creation. One of the main characteristics of symbolism about art that it distinguishes the concept from the previous Cassirer’s symbolic concepts, particularly medieval, in his opinion, that art is really symbolic, but the symbolism of art should be understood not in transcendental but immanent sense. S. Langer in "Philosophy in a new key: A Study in the Symbolism of Reason, Rite, and Art", continuing the Cassirer’s line on the recognition of the symbolic nature of human existence and the view of man as the "symbolic animal", along with an analysis of the symbolism of language, which it defines as discursive, consider the symbolism of visual forms, which he calls presentations, or re discussion, referring to him the sphere of art. Analyzed concepts demonstrate strong scientific interest to the question of symbolism in human culture, and emphasize the relevance of treatment to this issue.